Genomic characterization of dengue virus serotype 2 during dengue outbreak and endemics in Hangzhou, Zhejiang (2017–2019) - Sun, Hua; Yao, Wenwu; Siddique, Abubakar; He, Fan; Yue, Min (Frontiers in Microbiology, 2023)
Introduction Dengue fever (DF) is a mosquito-borne viral disease caused by the dengue virus (DENV). In recent years, Hangzhou has undergone a DF epidemic, particularly in 2017, with an outbreak of 1,128 patients. The study aimed to investigate the genetic diversity and molecular evolution among the DF clinical isolates during and after the outbreak to aid in mapping its spread. Methods To understand the genetic diversity, 74 DENV-2 strains were isolated from DF epidemic cases between 2017 and 2019. Combining whole genome sequencing (WGS) technology, additional phylogenetic, haplotype, amino acid (AA) substitution, and recombination analyses were performed. Results The results revealed that strains from 2017 were closely related to those from Singapore, Malaysia, and Thailand, indicating an imported international transmission. Local strains from 2018 were clustered with those recovered from 2019 and were closely associated with Guangzhou isolates, suggesting a within-country transmission after the significant outbreak in 2017. Compared to DENV-2 virus P14337 (Thailand/0168/1979), a total of 20 AA substitutions were detected. Notably, V431I, T2881I, and K3291T mutations only occurred in indigenous cases from 2017, and A1402T, V1457I, Q2777E, R3189K, and Q3310R mutations were exclusively found in imported cases from 2018 to 2019. The recombination analysis indicated that a total of 14 recombination events were observed. Conclusion This study may improve our understanding of DENV transmission in Hangzhou and provide further insight into DENV-2 transmission and the local vaccine choice.